Nghiên cứu và ứng dụng một phương pháp thống kê nhiều chiều trong y học - Hoa, Nguyen Quang; Hoa, Nguyen Tuan; Hung, Nguyen Van (Journal of Computer Science and Cybernetics, 2018)
In this paper, we study a method of analyzing three dimensional contingency tables and apply this method in biometry. Concretely, we detect the connection between the dust measure, the SO2 measure and the lung diseases, the work has been done for the contract with a researching group of the Medical University of Hanoi. The results are suitable to  those have been got from other medical researchs and have been well appreciated.